A Narrow Optical Gap Small Molecule Acceptor for Organic Solar Cells. Issue 1 (3rd September 2012) - Fang, Yuan; Pandey, Ajay K.; Nardes, Alexandre M.; Kopidakis, Nikos; Burn, Paul L.; Meredith, Paul
<x xml:space="preserve">Abstract</x> A new, strongly absorbing narrow optical gap small molecule acceptor YF25 is reported. When YF25 is blended with the archetypal donor P3HT, significant photocurrent red of the polymer optical gap is produced in addition to the normal response generated by the donor polymer. Using EQE and TRMC measurements we show that the additional photocurrent red of the donor edge is derived from excitation of the electron acceptor and subsequent hole‐transfer to P3HT. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>